Psychological Safety as a Catalyst for Healthcare Team Performance: Mediating Roles of Communication and Mental Health in Crisis Contexts - Ardiansyah, Fuad; Cahyono, Maria Yuni Megarini; Adiawaty , Susi (Indonesian Scientific Publication, 2024)
The COVID-19 pandemic placed unprecedented pressures on global healthcare systems, particularly frontline workers. This study examines how psychological safety influences team performance through the mediating roles of communication satisfaction and mental health among Indonesian healthcare professionals. A mixed methods approach involving surveys with 177 workers and interviews with 27 participants revealed that psychological safety significantly predicted team performance, partly through communication and well-being. Respondents frequently reported moderate quality of life, with qualitative findings highlighting fear of infection, communication challenges, emotional strain, and supportive peer dynamics. These results underscore the need to embed psychological safety frameworks into crisis protocols, ensuring effective communication, mental health support, and responsive leadership. The study proposes a multi-level model contextualized within Indonesian healthcare that offers practical strategies for improving team performance in resource-limited environments.